2017
DOI: 10.1590/s0104-12902017166561
|View full text |Cite
|
Sign up to set email alerts
|

Clima motivacional hacia el deporte y su relación con hábitos de ocio digital sedentario en estudiantes universitarios

Abstract: Clima motivacional hacia el deporte y su relación con hábitos de ocio digital sedentario en estudiantes universitarios Motivational climate in sport and its relationship with digital sedentary leisure habits in university students ResumenEl uso abusivo de videojuegos se asocia a consecuencias negativas para la salud, como son problemas músculo-esqueléticos, patología ocular o problemas cognitivos y emocionales. Ante esta problemática, múltiples estudios han demostrado como un estilo de vida activo mediante la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
1
9
0
10
Order By: Relevance
“…These subjects also do physical activity with friends and co-workers, both in municipal facilities or at home. About this basis, Sicilia et al (2014) showed a greater strength towards PASP in people who do it as a mean of satisfaction and amusement, although the percentages of active participants increase when intrinsic and extrinsic motivations are combined (Cerasoli, Nicklin, & Ford, 2014;Chacón et al, 2017;Owen, Astell-Burt, & Lonsdale, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…These subjects also do physical activity with friends and co-workers, both in municipal facilities or at home. About this basis, Sicilia et al (2014) showed a greater strength towards PASP in people who do it as a mean of satisfaction and amusement, although the percentages of active participants increase when intrinsic and extrinsic motivations are combined (Cerasoli, Nicklin, & Ford, 2014;Chacón et al, 2017;Owen, Astell-Burt, & Lonsdale, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…The second contribution is associated with the importance of promoting adaptive motivational patterns for learning within different individuals in order to enhance their adherence to physical activity. Teachers who create ego orientations at school could generate negative effects for students [8,46].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, self-determination theory and achievement goal theory have been the main theories to explain the motivational processes that operate in the behaviours of students and athletes in different contexts [6][7][8]. Self-determination theory posits that the motivation to enact a task is expressed along a continuum, which varies according to the degree of self-determination of the subject.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the care of the body and body image is of great social relevance Cachón, Cuervo, Zagalaz, & González, 2015;Chacón et al, 2017;López, Ahmed & Díaz, 2017;Morrison, Kalin, & Morrison, 2004;O'Dea, & Abraham, 2000;Zurita et al, 2015. In childhood, and especially in adolescence, lots of self-esteem problems arise stemming from the changes the body experiences during these years.…”
Section: Introductionmentioning
confidence: 99%